Pelestarian Tari Mangaru Sebagai Bentuk Kearifan Lokal pada Siswa Sekolah Dasar - Irwan, Irwan; Wahyudin, Amal; Sumantri, Sri; Faslia, Faslia; Agus, Jufri; Amelia, Amelia; Damayanti, Atun; Yusfita, Yusfita; Citra, Devi (Universitas Pahlawan Tuanku Tambusai, 2024)
The Mangaru Dance Tradition is one of the government art dances during the Buton Sultanate which depicts patriotism, nationalism and solidarity between kingdoms or sultanates. The purpose of this service is to find out the preservation of the Mangaru dance as a form of local wisdom of the Buton tribe for elementary school students and to find out the educational values ​​of elementary school children in the implementation of the Mangaru Dance tradition in the Buton Islands, especially at SD Negeri 2 Katobengke, Betoambari District, Baubau City. The results of this service illustrate that the implementation of the Mangaru dance tradition has educational values ​​for elementary school children such as instilling in children a love of culture, having ethics, stimulating motor development, children's cognitive development, language development, social emotional development and children's art development. The educational values ​​in the Mangaru Dance tradition are fully accumulated in the Mangaru Dance performance. The Mangaru Dance can be preserved by stimulating children to introduce and learn the Mangaru dance from an early age at all levels of school.